Assessment of bitter yam (dioscorea dumentorum [kunth] pax) production in Oyo state, Nigeria (2023)
Production of bitter yam (Discoreae dumentorum [Kunth.] Pax) is low in Oyo State, Nigeria. Two varieties are mainly cultivated, but there is limited information on factors responsible for low production and varietal preferences among farmers. This study investigated the demography, farming practices and differential proximate compositions as probable causes of low production of bitter yam in Oyo State. One hundred and twenty (120) copies of structured questionnaire were administered to selected respondents. Multistage sampling was used in selecting respondents in Oyo state from local government areas constituting four agricultural zones and 12 villages to collect demographic, production-related information, and constraints to production. Data were analyzed using descriptive statistics as well as analysis of variance (ANOVA). The result revealed that although bitter yam cultivation in Oyo state was male dominated (70%), majority of the farmers were old (57%), married (72%) and poorly educated (55%). Its production was for subsistence, and it was mainly grown in intercrop with other yam species. Ranked production constraints indicated poor marketability as the most extremely severe constraint, followed by labour unavailability and storage inadequacies. White bitter yam variety with superior basic proximate composition than Yellow Yam was preferred for cultivation. Subsistence production of bitter yam in Oyo state could be up-scaled through government intervention via farmer-centered education and public awareness and provision of infrastructure to facilitate cultivation, transportation, and storage.